Design And Optimi Z Ation Of Solar Power Plant Consisted Of Tracking Concentrator Photovoltaic System Based On Computational Analysis - Oon, Li Voon (2021)
The deterioration of overall electrical generation of solar power plant (SPP) as a result of optical losses via shadowing between adjacent CPV systems. The optical loses occur due to an inappropriate distribution of space for concentrator photovoltaic system (CPV) systems in the solar farm. An increase in the separation distance between adjacent CPV systems can reduce the deterioration of the overall electrical generation. Although this method can solve the existing problem, this causes an increase in land-related costs as a result of the ineffectiveness in land utilization. Thus, optimization of the layout design in the SPP is crucial towards the achievement of the best trade-off between land utilization and energy generation. The levelized cost of electricity (LCOE) of the SPP must be competitive in solar energy field to garner the interest from possible investors for its future development. In this research work, a newly developed computational algorithm has been presented to carry out the CPV field layout optimization process. This algorithm utilizes the local meteorological data, including the consideration of shadowing effect, land aspect ratio (LAR) and the cost of land. In this dissertation, a case study has been conducted in Kota Kinabalu, Malaysia based on different condition such as D ew /L ratio, D ratio, LAR and land cost to assess the performance ns /L of CPV system in the SPP configuration. for both square array and staggered array According to the results obtained through the case study, the optimized field layout for CPV systems for LAR of 1 is a staggered array layout configuration with the ho lds D ew /L ratio of 2.50 at spacing angle of 45 degree, the lowest value of LCOE.